2019
DOI: 10.1001/jama.2019.0710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient-Centered Transitional Care Services on Clinical Outcomes in Patients Hospitalized for Heart Failure

Abstract: Health care services that support the hospital-to-home transition can improve outcomes in patients with heart failure (HF). OBJECTIVE To test the effectiveness of the Patient-Centered Care Transitions in HF transitional care model in patients hospitalized for HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
270
1
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(293 citation statements)
references
References 30 publications
2
270
1
20
Order By: Relevance
“…A study of an inpatient geriatric consultation service similar to one of the major components of our intervention showed positive effects on several measures, but did not reduce 30‐day readmissions . A recent randomized trial of another intervention similar to the STAR program in patients with heart failure with a mean age of 78 years also failed to demonstrate an effect on 30‐day readmissions and returns to the ED …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A study of an inpatient geriatric consultation service similar to one of the major components of our intervention showed positive effects on several measures, but did not reduce 30‐day readmissions . A recent randomized trial of another intervention similar to the STAR program in patients with heart failure with a mean age of 78 years also failed to demonstrate an effect on 30‐day readmissions and returns to the ED …”
Section: Discussionmentioning
confidence: 74%
“…37 A recent randomized trial of another intervention similar to the STAR program in patients with heart failure with a mean age of 78 years also failed to demonstrate an effect on 30-day readmissions and returns to the ED. 38 We learned several lessons that may be valuable for implementing care transition interventions in the high-risk geriatric population. First, the intervention was not as robust as it could have been.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 17 of the 25 studies were conducted in North America [17-22, 24-27,29,31,34,37-40], three in Europe [23,30,35], three in China [16,28,32], and two in Iran [33,36]. Thirteen of the 25 studies did not report racial ethnicity [16,20,21,23,24,26,28,30,32,33,35,36,38]. The sample size ranged from 38 [24] to 3462 [19], and the average patient age was between 65 [36] and 82 years [27,30].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Subjects presented with various HF types: two studies reported on end-stage HF [28,32], three on chronic HF [16,23,33], two on congestive HF [21,37], one on decompensated HF [29], and the remaining 17 on HF [17][18][19][20]22,[24][25][26][27]30,31,[34][35][36][38][39][40]. To identify HF severity, we considered the New York Heart Association (NYHA) class and left ventricle ejection fraction (LVEF).…”
Section: Type and Severity Of Hfmentioning
confidence: 99%
“…Although early post-discharge follow-up is recommended following HF hospitalization, such transitional care strategies have not conclusively improved clinical outcomes. 6,9 These inconsistent results may stem from the difficulty and variability in the assessment of congestion by clinicians. 5 Haematocrit represents a widely available and inexpensive laboratory test that can be easily ordered in the outpatient clinic.…”
mentioning
confidence: 99%